Refocusing On Reading: Strategies To Enhance Reading And Analytical Skills In History Courses - Perri, Michael (Teaching History: A Journal of Methods, 2010)
The digital age has changed American society, which means history instructors face a different reality in their classrooms. With their cell phones, blackberries, iPods, digital games, computers, and the Internet, Americans have an unprecedented number of digital distractions. Few people have time to read anymore. Meanwhile, the new diversions have not displaced the popularity of television. According to a study conducted by the National Endowment for the Arts (NEA), Americans age 15 and older spend about half of their total daily leisure time watching TV, while "15- to 24- year-olds spend less than three percent of their daily leisure time reading, and 25 to 34-year-olds spend roughly four percent." College students are no less affected, and arguably more so. They read less in their leisure time than did earlier generations, and consequently they read less proficiently. The National Assessment of Adult Literacy (NAAL) gave a reading comprehension test to 19,200 Americans, ages sixteen and above, and found that declines in "proficient" readers are steepest among the best-educated groups. Between 1992 and 2003, the study reported "a 20 percent rate of decline for adults with a graduate school experience and a 22 percent rate of decline for other college graduates."1 So how should history instructors respond? The answers must be measured because modern means of instruction can enhance education. The narratives and visuals of documentaries can stimulate learning, and the Internet vastly increases access to information. However, these digital advances have a downside. The new media cannot replace the thoughtful reading of scholarly texts and their use unavoidably decreases the customary focus on reading assignments in history courses. To compensate for this shift, educators should make corrective adjustments. Such adjustments do not imply eschewing the Internet as a resource and educational tool, nor do they suggest avoiding the occasional use of documentaries. They simply require instructors to renew their efforts to teach traditional reading and analytical skills in our age of ever-changing technologies. This article presents strategies to foster such skills through "main-point" and "reflective-reading" assignments. It also assesses the value of active-reading instruction. I have designed and used these strategies and assignments in college-level history courses of roughly twenty to thirty students.